Distribution of the Abundace Fur Shell (Anadara inflata) in Intertidal Coastal Water of Tanjung Balai Asahan North Sumatera province - Ruth Natalia. S; Syafruddin Nasution; Joko Samiaji (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted from January-February 2013 in the coastalwaters in Tanjung Balai Asahan, North Sumatera Province. The aim of thisresearch was to understand the pattern distribution and density of fur shells (A.inflate). Survey method was applied on this research where data were obtained bydirect observation in the field. The samples of shells fur were analyzed in thelaboratory of Marine Biology, of Riau University. Water quality parameters weremeasured in situ.The results showed that the pattern distribution of fur shells (Anadarainflata) was in a group. The density of A. Inflata ranged from 125 ind/m2 to 136ind/m2. These values were not significant different when they were statisticallytested. Moreover, the water quality parameters were in the sufficient range formarine fur shells (A. inflata) survival.Keywords: Anadara inflata, distribution, Tanjung Balai Asahan, density